(untitled) (Revista Contexto & Saúde, 2025)
Objective: To understand patient-centered care from the perspective of adult inpatients during hospitalization. Method: This qualitative, exploratory, and descriptive study was conducted with 31 patients admitted to the medical and surgical units. Data were collected through recorded interviews, which were transcribed, validated, and processed using Iramuteq software. Categories were constructed based on the Institute of Medicine’s guiding principles for patient-centered care, and content analysis was applied. The study complied with ethical principles for research involving human subjects and was approved by the Institutional Review Board of the Federal University of Rio Grande do Sul (CAAE No. 73679623.4.0000.5324). Results: Four categories emerged: respecting patient preferences; information, education, and integration of care; physical comfort and emotional support; and access to care. Including patients and family members in the care process is essential to ensure greater safety, understanding, and support. Conclusions: The study offered insights into patient-centered care from the perspective of patients and families, revealing both strengths and obstacles to its consolidation. It highlights the importance of patients’ role as active participants in creating a safe environment and improving clinical conditions.